2005
DOI: 10.1002/ccd.20453
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐eluting stents for coronary bifurcations: Bench testing of provisional side‐branch strategies

Abstract: The objective of this study was to bench-test provisional bifurcation stenting strategies to provide insights on how best to perform these with drug-eluting stents (DESs). Bifurcation stenting with DESs reduces restenosis compared with bare metal stents (BMSs). Outcomes with a single DES are better than with two DESs but if the main branch is stented, there needs to be a reliable strategy for provisionally stenting the side-branch with full ostial scaffolding and drug application. Stents were photographed in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(79 citation statements)
references
References 9 publications
1
77
0
1
Order By: Relevance
“…It has been suggested that postdilatation would facilitate subsequent SB access. 14 We found that the need for TLR was Ͻ2% after 6 months, indicating that the need for subsequent SB access was low.…”
Section: Clinical Outcomesmentioning
confidence: 66%
See 1 more Smart Citation
“…It has been suggested that postdilatation would facilitate subsequent SB access. 14 We found that the need for TLR was Ͻ2% after 6 months, indicating that the need for subsequent SB access was low.…”
Section: Clinical Outcomesmentioning
confidence: 66%
“…Meticulous bench testing has shown that stent deformation is consistently seen after opening of a stent, but this deformation can be corrected by FKBD. 13,14 Therefore, the present study compared FKBD and no FKBD to investigate both the clinical and angiographic effects of routine opening of the MV stent struts at the SB ostium in bifurcation lesions treated with MV stenting.…”
Section: Niemelä Et Almentioning
confidence: 99%
“…20,21 There are theoretical advantages of the culotte over a provisional-T strategy in lesions with large SB, such as SB protection and full ostial coverage. [22][23][24] In left main bifurcation, lesions culotte technique has compared favorably with the provisional strategy but was associated with increased major adverse cardiac event (mainly because of increased target vessel revascularization) when compared with the DK crush technique. 21,25,26 The 2 kissing balloon inflations intrinsic to the DK crush technique may improve ostial SB stent apposition resulting in less restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…The specific mechanism underlying restenosis at SB ostium is at the moment not completely clear and presumably many factors are involved. 1,8,[11][12][13] The British Bifurcation Coronary study 14 randomised 500 patients with coronary bifurcation lesion for simple or complex strategy using Paclitaxel DES. The simple group had provisional stenting where as the complex group had crush or Culotte technique with two DES.…”
Section: Recent Studies On Bifurcation Percutaneous Coronary Intervenmentioning
confidence: 99%